PELATIHAN KOMUNIKASI VERBAL DAN NON-VERBAL EFEKTIF ANTARA DOKTER, PERAWAT, PASIEN, DAN KELUARGA PASIEN DI RUMAH SAKIT JIWA DR. SOEHARTO HEERDJAN JAKARTA - Bugi, Bugi Satrio (Universitas Esa Unggul, 2018)
AbstractIntroduction: In relation to efforts to improve the educational process and information provided to patients and families of the sand, it is necessary to improve the skills and skills of hospital staff about effective verbal and non-verbal communication between physicians, nurses, patients and families. does not include all staff who provide education, where the requirements of educators must follow effective and certified communication training. Activity Objective: to provide theoretical and practical knowledge to educators on how to establish effective verbal and non-verbal communication between physicians, nurses, patients, and the families of patients at Dr. Soul Mental Hospital. Soeharto Heerdjan Jakarta. Method of Implementation: This activity is conducted in 4 (four) sessions, namely: 1) Pre-test by giving questionnaire to audience related to effective communication, 2) delivery of verbal and non verbal communication materials effective, 3) Effective communication practice (Role Play - Simulation), and 4) Post-test by giving the audience an effective communication-related kusioner. Results: Educational personnel of Dr. Mental Hospital. Suharto Heerdjan Jakarta is able to provide health education and communicate well, accurately, clearly, completely, accurately, and can be understood by the recipient (communicant) thereby reducing errors and improving the improvement of health services for patients and between officers in the hospital.Â Keywords: effective verbal and non-verbal communication, educator, health educationÂ AbstrakPendahuluan: Sehubungan dengan upaya peningkatan proses edukasi dan informasi yang diberikan kepada pasien dan keluarga pasirn, diperlukan peningkatan kemampuan dan keterampilan petugas rumah sakit tentang komunikasi verbal dan non-verbal efektif antara dokter, perawat, pasien, dan keluarga pasien di Rumah Sakit Jiwa Dr.Soeharto Heerdjan Jakarta. Pelatihan komunikasi efektif yang sudah dilaksanakan sebelumnya belum mencakup seluruh staf yang memberikan edukasi, dimana persyaratan tenaga edukator harus mengikuti pelatihan komunikasi efektif dan bersertifikat. Tujuan Kegiatan: memberikan pengetahuan secara teori dan praktikal kepada tenaga edukator tentang cara menjalin komunikasi verbal dan non-verbal efektif antara dokter, perawat, pasien, dan keluarga pasien di Rumah Sakit Jiwa Dr. Soeharto Heerdjan Jakarta. Metode Pelaksanaan: Kegiatan ini dijalankan dalam 4 (empat) sesi, yaitu: 1) Pre-test dengan memberikan kuisioner kepada audiens terkait komunikasi efektif, 2) Penyampaian materi komunikasi verbal dan non-verbal efektif ,3) Latihan komunikasi efektif (Role Play â Simulasi), dan 4) Post-test dengan memberikan kusioner kepada audiens terkait komunikasi efektif. Hasil: Tenaga edukator Rumah Sakit Jiwa Dr. Soeharto Heerdjan Jakarta mampu memberikan pendidikan kesehatan dan berkomunikasi dengan baik, tepat, jelas, lengkap, akurat, dan dapat dipahami oleh penerima (komunikan) sehingga mengurangi kesalahan dan peningkatan perbaikan pelayanan kesehatan bagi pasien dan antar petugas di rumahsakit.Â Kata kunci: komunikasi verbal dan non-verbal efektif, tenaga edukator, pendidikan kesehatan